2014
DOI: 10.1038/srep06783
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Distribution of Surgical Site Infection in Mainland China: A Meta-Analysis of 84 Prospective Observational Studies

Abstract: Surgical site infection (SSI) is one of the most common surgical complications in the world, particularly in developing countries. This study aimed to estimate the incidence and distribution of SSI in mainland China. Eighty-four prospective observational studies (82 surveillance studies, 1 nested case control study, and 1 cohort study) were selected for inclusion in this meta-analysis. The average incidence of SSI in mainland China was 4.5% (95% CI: 3.1–5.8) from 2001 to 2012 and has decreased significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
77
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 47 publications
15
77
2
1
Order By: Relevance
“…Previous studies have suggested that the incidence of HCAI tends to be lower in eastern coastal regions relative to those of the midlands and remote western regions because the eastern coastal areas enjoy stronger economies and more abundant healthcare resources [5, 31]. However, an east-to-west gradient was not noted in our geographic mapping of the cumulative VAP incidence.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have suggested that the incidence of HCAI tends to be lower in eastern coastal regions relative to those of the midlands and remote western regions because the eastern coastal areas enjoy stronger economies and more abundant healthcare resources [5, 31]. However, an east-to-west gradient was not noted in our geographic mapping of the cumulative VAP incidence.…”
Section: Discussionmentioning
confidence: 66%
“…Most of the included studies came from Western countries (United States, Germany, Switzerland, United Kingdom) and were conducted in large academic medical centers, and therefore may not adequately represent patients living in non‐Western countries or more rural areas. SSI rates are significantly higher in developing regions of the world, as compared to the United States and other western countries; this may be due to less strictly enforced hospital infection control standards and a lack of required resources in rural ambulatory clinics . Additionally, in rural areas, facial fractures are more likely to occur in highly contaminated environments, in the presence of livestock, agriculture, zoonotic infectious diseases, dirt, and other foreign bodies, which could increase the risk of infection and require additional postoperative antibiotic prophylaxis …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of various groups of microorganisms varies considerably [5][6][7][8][9][10][25][26][27][28][29]. This proves the necessity of carrying out microbiological monitoring in every surgery hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infections (SSIs) are the most common type of nosocomial infection among surgical patients. [4][5][6][7]. SSIs is a wound infection that occurs following an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%